Routine Testing of Liver Function Before and After Elective Laparoscopic Cholecystectomy: Is It Necessary? - Ahmad, Nasir Zaheer (Society of Laparoendoscopic Surgeons, 2011)
BACKGROUND AND OBJECTIVES: Liver function tests (LFTs) include alanine aminotransferase (ALT), aspartate aminotransferase (AST), gamma-glutamyl transpeptidase (GGT), alkaline phosphatase (ALP), and bilirubin. The role of routine testing before and after laparoscopic cholecystectomy was evaluated in this study. PATIENTS AND METHODS: A total of 355 patients were retrospectively analyzed by examining the LFTs the day before, the day after, and 3 weeks after the surgery. The Wilcoxon signed-rank test and Student t test were performed to determine statistical significance. RESULTS: Alterations in the serum AST, ALT, and GGT were seen on the first postoperative day. Minor changes were seen in bilirubin and ALP. An overall disturbance in the LFTs was seen in more than two-thirds of the cases. Repeat LFTs performed after 3 weeks on follow-up were found to be within normal limits. CONCLUSION: Mild-to-moderate elevation in preoperative LFTs may not be associated with any deleterious effect, and, in the absence of clinical indications, routine preoperative or postoperative liver function testing is unnecessary.